Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/app.49980
|View full text |Cite
|
Sign up to set email alerts
|

On the potential of polyetheretherketone matrix composites reinforced with ternary nanolaminates for tribological and biomedical applications

Abstract: We report the synthesis and characterization of PEEK-MAX (Ti 3 SiC 2 , Ti 3 AlC 2 , and Cr 2 AlC), and PEEK-MoAlB composites by hot-pressing. Detailed microstructure analysis by scanning electron microscopy showed that Ti 3 SiC 2 particles are well dispersed in the PEEK matrix after the addition of 5 vol% Ti 3 SiC 2 but at higher concentration (≥10 vol%), the Ti 3 SiC 2 particles segregated at the phase boundaries and formed interpenetrating micro-networks. PEEK-Ti 3 AlC 2 and PEEK-MoAlB composites also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 38 publications
(145 reference statements)
2
15
0
Order By: Relevance
“…Similarly segregation of Ti 3 SiC 2 , Ti 3 AlC 2 , and MoAlB particles were also observed in the PEEK matrix fabricated at the same temperature. 46 Bastan et al 47 also observed similar segregation of Sr substituted Hydroxyapatite particles in PEEK matrix.…”
Section: Microstructure Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…Similarly segregation of Ti 3 SiC 2 , Ti 3 AlC 2 , and MoAlB particles were also observed in the PEEK matrix fabricated at the same temperature. 46 Bastan et al 47 also observed similar segregation of Sr substituted Hydroxyapatite particles in PEEK matrix.…”
Section: Microstructure Analysismentioning
confidence: 79%
“…Hot-pressed pristine PEEK samples showed a porosity of ⁓1.68% 46 and PEEK composites with 5 vol% addition of DDGS500, Mo, and Xonotlite had a porosity of $ 2.48%, $ 1.70%, and $ 3.14% respectively, as shown in Figure 5a. The addition of 10 and 20 vol% reinforcements with PEEK increased the porosity of the samples gradually.…”
Section: Porosity Hardness and Mechanical Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…High-performance polyetheretherketone (PEEK) composites have attracted particular attention for the potential engineering applications, especially in the biomedical field for human bone replacement, because of their superior physicochemical characteristics, biocompatibility, and bone-like stiffness. 1,2 PEEK composites with the addition of multiwalled carbon nanotubes (MWCNTs) exhibited better efficacy in biomedical uses with reduced toxicity and improved mechanical and thermal stability due to their large surface area, low density, and higher tensile properties. 3,4 The PEEK/MWCNT composites have been manufactured by several methods to address the role of MWCNTs in PEEK, including solution mixing, 5 compounding and injection molding, 6 chemical modification of CNTs 7 and melt blending of PEEK with MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, long fibers-most often carbon fibers 5 or glass fibers 4 -are associated with the PEEK matrix. In addition, lamellar or particulate reinforcements such as graphite, 6,7 (Sukumaran, Schlarb, and Baets), molybdenum disulfide, 8 silicon carbide, 9 silicon oxide, 10 and titanium silicocarbide 11,12 have been incorporated. In other cases, it has been proved that polymer blends, through the addition of polyethersulfone 13 and polyetherimide 14 fillers, enhance the thermomechanical properties of PEEK.…”
Section: Introductionmentioning
confidence: 99%